The rise of counterfeit medication: an emerging threat? - Larik, Muhammad Omar (Journal of the Pakistan Medical Association, 2024)
Madam, The definition of health is far more complex than initially imagined. As per the World Health Organisation (WHO), the “health” is defined as complete physical, mental, and social well-being instead of simply the absence of any disease.1 In the era of modern healthcare, medications are undoubtedly important in ensuring well-being worldwide. Despite monumental advances within the medical industry, the rise of counterfeit medication has become an emerging threat. Counterfeit medications are known as products sold with the deception of providing therapeutic benefits but consist of little-to-no active ingredients, which may or may not be harmful.2 Traditionally, the regulation of drug distribution falls under the responsibility of the health authorities of the relevant region, such as the Drug Regulatory Authority of Pakistan (DRAP). Reports of an escalating influx of counterfeit medications into Pakistan have recently created pivotal concerns within the local communities.3,4 In Karachi, officials seized a large quantity of cefixime and aspirin suspension powders, which were found to be “fake and spurious”.3 The counterfeit medication was created by repackaging locally-manufactured powder into branded bottles, which were subsequently sold across the city. In another case affecting various cities in Pakistan, a factory was illegally manufacturing spurious medication, leading to a nationwide cautionary announcement to avoid the purchase of affected drugs, including the lifesaving meropenem, among various other cephalosporin drugs.4 The distribution of counterfeit medications can have drastic consequences for the population. Patients in critical conditions may suffer further harm due to defective treatment, as a result of the failure of substandard products.5 Moreover, counterfeit drugs manufactured with inappropriate doses or concentrations may lead to fatal adverse effects, such as respiratory paralysis or death.5 In order to address this pressing issue, the national authorities must take proactive measures to tackle the production and distribution of counterfeit medication: There is a need for frequent and strict raids integrated within each city of Pakistan, in which local pharmacies have their inventory tested for substandard or inappropriate substances. Secondly. The import of medications must also be strongly monitored, in order to prevent the arrival of counterfeit or unregistered medications from foreign regions. It is recommended that the authorities establish pharmaceutical support programs for those individuals who cannot afford proper medications and eventually resort to purchasing substandard medication.